Wuling Mountains Function as a Corridor for Woody Plant Species Exchange Between Northern and Southern Central China - Wang, Congrong; Zhou, Tianyang; Qin, Yuanzhi; Zhou, Gang; Fei, Yanan; Xu, Yaozhan; Tang, Zhiyao; Jiang, Mingxi; Qiao, Xiujuan (Frontiers in Ecology and Evolution, 2022)
Wuling Mountains range from the northeast to southwest in Central China, a region with high habitat complexity and diversity which supports substantial plant species diversity. Connecting the northern subtropics to the mid-subtropics, Wuling Mountains also link the floras of Eastern and South-Western China. Despite a long-standing interest in the important role Wuling Mountains play in species exchange, patterns of diversity in Wuling and their underlying drivers are still not well understood. Here, the spatial distribution of woody plant species in this region is investigated and the role of Wuling Mountains in structuring biodiversity in surrounding areas explored.Detailed distribution data for woody plant species in China were collected and mapped onto a raster grid of the Wuling Mountains and adjacent regions (a total of 820,000 km2) to analyze spatial patterns in species diversity, including α-diversity (species richness) and β-diversity (βsor). Canonical redundancy analysis was used to illustrate spatial patterns and species-environment relationships.Mountainous areas in the study region have high species richness as compared to other areas. Species exchanges occurred at a greater rate latitudinally versus longitudinally, especially in Wuling Mountains. This suggests Wuling Mountains may be an important ecological corridor for woody species, linking Northern and Southern Chinese floras. The study region was divided into six bioregions based on species composition: the Wuling Mountains Region, Nanling-Xuefengshan Mountains Region, Qinling-Dabashan Mountains Region, Sichuan Basin Region, Jianghan Plain Region and Yungui Plateau Region. The Wuling Mountains Region acted as an ecological corridor for woody species, linking Northern and Southern China, and fostering biodiversity exchange and conservation in Central China.